2009
DOI: 10.1073/pnas.0906005106
|View full text |Cite
|
Sign up to set email alerts
|

Role of human noncoding RNAs in the control of tumorigenesis

Abstract: Related studies showed that the protein PSF represses protooncogene transcription, and VL30 -1 RNA, a mouse noncoding retroelement RNA, binds and releases PSF from a proto-oncogene, activating transcription. Here we show that this mechanism regulates tumorigenesis in human cells, with human RNAs replacing VL30 -1 RNA. A library of human RNA fragments was used to isolate, by affinity chromatography, 5 noncoding RNA fragments that bind to human PSF (hPSF), releasing hPSF from a protooncogene and activating trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 13 publications
2
137
0
2
Order By: Relevance
“…A previous study suggested that a number of lncRNAs may be involved in the development and metastasis of cancer (7). LncRNA-imprinted maternally expressed transcript (non-protein coding) (H19), initially reported in 1991 by Bartolomei et al (8), was identified to be expressed at increased levels in extraembryonic tissues, embryonic tissues and the majority of fetal tissues; however, the expression level of lncRNA H19 is markedly decreased following birth (9).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that a number of lncRNAs may be involved in the development and metastasis of cancer (7). LncRNA-imprinted maternally expressed transcript (non-protein coding) (H19), initially reported in 1991 by Bartolomei et al (8), was identified to be expressed at increased levels in extraembryonic tissues, embryonic tissues and the majority of fetal tissues; however, the expression level of lncRNA H19 is markedly decreased following birth (9).…”
Section: Introductionmentioning
confidence: 99%
“…This result implies that MALAT1 regulates the post-transcriptional processing or modification of RNA. MALAT1 binds to PSF (polypyrimidine tract binding protein-associated splicing factor) and prevents PSF from binding to the transcriptional regulatory region of the oncogene CAGE6, which stimulates the abundant transcription of GAGE6 and thus promotes tumorigenesis [63].…”
mentioning
confidence: 99%
“…The present study focused on the role L1 RNA may serve in lung carcinogenesis without HBV infection, which is different from HBx-LINE-1 causing hepatocarcinogenesis (16). It has previously been demonstrated that L1PA16 RNA binds to PSF protein, which is part of the LINE retrotransposons family (10). Therefore, L1 RNA, although it shares no sequence similarity with L1PA16 RNA, may bind to PSF.…”
Section: Binding Ability Of L1 Rna and Psf Protein In Vitromentioning
confidence: 99%
“…The RBD and DBD function independently and their novel mechanisms for reversible gene transcription mediated by PSF protein and noncoding RNA have been investigated. It has been demonstrated that their transcription is activated by the release of PSF protein from the repressed proto-oncogene G antigen 6 (GAGE6) by five PSF-binding noncoding RNA fragments (10). This indicates that the regulatory activity of noncoding RNA in tumorigenesis occurs through its binding to the RBD of PSF and the consequent release of the transcriptionally repressed proto-oncogene from its DBD.…”
Section: Introductionmentioning
confidence: 99%